ANALISIS KELAS KEMAMPUAN PENGGUNAAN LAHAN DI AREAL SUB DAS RIAM KANAN KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Sumaryono, Sumaryono; Badaruddin, Badaruddin; Ruslan, Muhammad (Lambung Mangkurat University-Indonesia, 2024)
Inappropriate land use can result in changes in environmental conditions that have negative impacts on humans. Land use that is not in accordance with its capabilities can cause various disasters, such as excessive erosion, landslides, floods, droughts, and an increase in the area of critical land. The Riam Kanan sub-watershed is one of the sub-watersheds in Banjar Regency, South Kalimantan whose condition requires conservation because this area has varying slopes, so if the land is not managed properly, it can cause flooding and other natural disasters. Based on this, it is necessary to carry out research related to the Land Use Capability Classification. The aim of this research is to analyze inhibiting or limiting factors and to formulate land use capability classes. The highest slope percentage of 15 - 25% is found in Land Unit 3 (three) Block A, Land Unit 4 (four) Block B and Land Unit 2 (two) in Block D. The lowest slope percentage of 3-8% is found in Unit Land 1 (one) Block A, Land Unit 1 (one) Block B and Land Unit 3 (three) in Block C. Other Land Units have a slope percentage of 8-15%. Land Use Capability Classes (KPL) obtained from the analysis results are 3 (three) Land Use Capability Classes (KPL), namely 1). KPL II with Soil Depth Limiting Factor